Meta-Analysis: The Effect of Mathematical Resilience to Mathematical Problem Solving Ability - Tania, Nova; Mariani, Scolastika; Agoestanto, Arief; Susilo, Bambang Eko (SJME (Supremum Journal of Mathematics Education), 2024)
The aim of this research is to analyze the effect of mathematical resilience to mathematical problem solving abilities based on relevant articles. This research method uses meta analysis using OLS (Ordinary Least Square) to determine a simple linear regression equation and also using formula effect size to determine the measure of effect. The results of this research are that mathematical resilience has a positive effect to mathematical problem solving abilities of 44.488% with a simple linear regression equation, namely . The effect of mathematical resilience to mathematical problem solving ability is large, with average of effect size is 0.764. So, its conclude that mathematical resilience had positive large effect to mathematical problem solving ability.